1992
DOI: 10.1097/00012272-199206000-00007
|View full text |Cite
|
Sign up to set email alerts
|

From preventive health behavior to health promotion

Abstract: A concept analysis of preventive health behavior provided the foundation for this review of current health promotion research in nursing. Studies selected for review described or explained behavior for health promotion, illness prevention, or preventive health behavior. The major focus of this critical review is on the conceptualization and measurement of health promotion behaviors being investigated. Despite nursing's claim to an holistic idea of health, the biomedical model continues to influence indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Indicators of health within the concept of health promotion have been broadened to cover the positive aspects of health and well‐being 3 . Traditionally, health promotion research in nursing has been mainly directed toward the prevention of diseases and less to the positive and multidimensional constructs of health 4 …”
Section: Introductionmentioning
confidence: 99%
“…Indicators of health within the concept of health promotion have been broadened to cover the positive aspects of health and well‐being 3 . Traditionally, health promotion research in nursing has been mainly directed toward the prevention of diseases and less to the positive and multidimensional constructs of health 4 …”
Section: Introductionmentioning
confidence: 99%
“…4 Studies of disease and care management models that aim to limit "preventable" events by promoting self-management skills and maximizing adherence to standards of care demonstrate promise for reducing costs and improving care, 5 but more research is needed to determine which model and which components of each model generate the desired results. 2,[6][7][8][9][10] Two recently published review articles, one specific to diabetes, but neither isolating telephone interventions in their review, concluded that there was empirical evidence supporting the effectiveness of self-management training and disease management programs in improving disease control but that little is known about the individual intervention strategies. 11,12 The Diabetes Complications and Control Trial (DCCT), 13 which included telephone support, reported the longest follow-up and the most conclusive results but did not determine which components (eg, office visits, phone calls) of the intensive follow-up were most effective in lowering glycosated hemoglobin (HbA1c) and the improving microvascular complications.…”
Section: Introduction T He Care Of Individuals With Chronic Condi-mentioning
confidence: 99%
“…They identify that both are events or incidents, implying that some occurrence must take place prior to, or as a consequence of, the concept. From the relational statements (Table 2) and definitions of HP, antecedents of HP were discovered: (i) previous decisions and responsibility on health (Kulbok and Baldwin, 1992; Morgan and Marsh, 1998; Buetow and Kerse, 2001), (ii) beliefs, attitudes, behaviours and perceptions (Rosenstock 1974; Pender et al , 2002; Wu and Pender, 2002), (iii) change of healthy lifestyle (Rosenstock 1974; Wang et al , 2000; Pender et al , 2002; Wu and Pender, 2002) and (iv) health challenges (Moore and Williamson, 1984; Smith, 1990). These antecedents are similar in that they are influenced by social context.…”
Section: Methodsmentioning
confidence: 99%